Biphase in-situ injection-mixing type hydrogel adhesive coating material with biological membrane breaking and killing function and preparation method of biphase in-situ injection-mixing type hydrogel adhesive coating material
By using a biphasic in-situ injection-mixed hydrogel adhesive coating material, combined with EPS hydrolytic enzymes and antibacterial active components, an endoscopic catheter is used to achieve efficient destruction and killing of biofilms, solving the problem of insignificant biofilm removal in existing technologies and realizing efficient treatment of postoperative infections after bone implantation devices.
Patent Information
- Application Number
- CN202511310546.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2026-01-09
- Estimated Expiration
- 2045-09-15
AI Technical Summary
Existing technologies for biofilm removal are not very effective, are difficult and expensive, making it difficult to effectively treat postoperative infections of bone implant devices.
A biphasic in-situ injection-mixed hydrogel adhesive coating material is used. EPS hydrolytic enzyme and antibacterial active components are mixed and injected into the infection site through an endoscopic active material delivery catheter. The release of EPS hydrolytic enzyme destroys the biofilm, and the combination with antibacterial active components kills bacteria. The in-situ gelation of the adhesive coating is achieved by utilizing the Schiff base reaction.
It achieves efficient destruction of biofilm, significantly reducing the difficulty and cost of treating postoperative infections of bone implant devices. It is convenient, practical and universal, and avoids the harm caused by secondary surgery.
Smart Images

Figure CN121288030A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of bone infection treatment materials, in particular to a dual-phase in-situ injection mixed hydrogel adhesive coating material with biofilm breaking and killing functions and a preparation method thereof. BACKGROUND
[0002] Biofilm is a microorganism organized growth aggregate, is that bacteria irreversibly attach to the surface of inert or active entities, and through reproduction, differentiation, and secretion of polysaccharide matrix, a bacterial aggregate film is formed, which is very common on the surface of medical implant / instrument. And due to the wrapping of polysaccharide matrix and the like, the resistance of biofilm bacteria to antibiotics and host immune defense mechanisms is greatly improved compared to free bacteria. The direct result of the above phenomenon is that once a biofilm is formed on the surface of an implant / instrument, it is difficult to eradicate, and repeated treatment will cause a huge physiological and psychological burden on the patient.
[0003] As of now, the treatment measures for biofilm in the clinic mainly focus on thorough debridement, secondary surgery to replace implants, and the like. However, due to the limitations of insignificant effect, great difficulty, high cost, and the like, patients and doctors are eager for a new biofilm treatment strategy. The formation process of biofilm can be divided into five stages, mainly including reversible contact stage, irreversible contact stage, colony formation stage, biofilm maturation stage, and biofilm aging and shedding stage. The current research direction is mainly to achieve efficient prevention of biofilm formation by inhibiting bacterial adhesion in the early stage of biofilm formation. However, in actual clinical scenarios, the biofilm has generally already been formed, so the above strategy may not be applicable.
[0004] In view of the above problems, the present application provides a dual-phase in-situ injection mixed hydrogel adhesive coating material with biofilm breaking and killing functions and a preparation method thereof. By introducing EPS-dissolving enzyme with biofilm extracellular matrix (EPS) dissolving function and antibacterial active components into the hydrogel adhesive matrix, after forming a hydrogel adhesive layer on the surface of the already formed biofilm by in-situ injection, the EPS hydrolytic enzyme is released to destroy the EPS, so that the bacteria in the biofilm are released, and further combined with the released antibacterial active components to kill the released bacteria, achieving the purpose of treating biofilm. SUMMARY
[0005] The purpose of the present application is to provide a dual-phase in-situ injection mixed hydrogel adhesive coating material with biofilm breaking and killing functions and a preparation method thereof to solve the problem of insignificant effect of biofilm removal measures in the prior art. The present application realizes effective biofilm breaking and killing and efficient treatment of postoperative infection of bone implant instruments, and has obvious convenience, practicality and universality.
[0006] The present application realizes the following technical solutions: A preparation method of a two-phase in-situ injection mixed type hydrogel adhesive coating material with biofilm breaking function, comprising the following steps: 1) preparing a DA-CCs solution loaded with antibiotics and a hyaluronic acid oxidized solution loaded with EPS hydrolytic enzyme; 2) mixing and injecting the two solutions obtained in step 1) to the surface of the instrument at the infection site through an endoscopic active material delivery catheter, and then in-situ gelating the hydrogel adhesive coating material through Schiff base reaction; The endoscopic active material delivery catheter comprises a catheter tube, a field acquisition module, a liquid reservoir, a material mixing channel, an injection hole and a catheter controller assembly. The catheter tube is provided with an elastic tube segment at one end, and the end serves as an advancing end. The field acquisition module is arranged at the end of the advancing end, and is used for collecting and transmitting image information to a display device. Two liquid reservoirs are arranged in the catheter tube, and are used for respectively containing the DA-CCs solution loaded with antibiotics and the hyaluronic acid oxidized solution loaded with EPS hydrolytic enzyme obtained in step 1). The injection hole is arranged at the end of the advancing end. The material mixing channel is arranged in the catheter tube, and is used for mixing the solutions in the two liquid reservoirs and outputting from the injection hole. The catheter controller assembly is used for realizing bending control of the elastic tube segment.
[0007] Further, in step 1), the preparation method of the DA-CCs is as follows: Dopamine hydrochloride is used to perform catechol modification on carboxymethyl chitosan to obtain DA-CCs. Specifically, carboxymethyl chitosan and dopamine hydrochloride are dissolved in a solvent, 1-ethyl-(3-dimethylaminopropyl) carbonyl diimide (EDC) is added to the solvent under nitrogen protection for 30-60 min for stirring and activation, N-hydroxy succinimide (NHS) is added for coupling reaction, the obtained product is dialyzed, and freeze-drying is performed to obtain the DA-CCs.
[0008] Further, the dopamine hydrochloride (DA) concentration is 0.4-1.0 wt%, the carboxymethyl chitosan (CCs) has a molecular weight of 2000-50000 and a degree of carboxylation of 60-90%, and a concentration of 5-20 wt%; the solvent is a mixture of DMSO (dimethyl sulfoxide) and deionized water, with a ratio of 20 wt% DMSO and 80 wt% deionized water, the 1-ethyl-(3-dimethylaminopropyl) carbodiimide concentration is 0.05-0.12 wt%, the N-hydroxysuccinimide concentration is 0.04-0.12 wt%, the coupling reaction time is 12-48 hours, and the reaction is magnetically stirred at 200-400 rpm during the reaction; after the reaction is completed, the product is dialyzed with ultrapure water for 3-7 days, and the liquid is changed 3-5 times a day.
[0009] Further, in step 1), the DA-CCs concentration is 5-22 wt%; the antibiotic is one or more of glycopeptide, carbapenem, and quinolone, preferably glycopeptide, and more preferably vancomycin, and the addition amount is 0.5-1 wt%.
[0010] Further, in step 1), the EPS hydrolytic enzyme is one or more of PgaB (polyglucosamine subunit B), alginate lyase, linear polysaccharide lyase, β-(1,3) glucan lyase, dispersin B, Proteinase K, Staphopain A, Staphopain B, Streptococcalcysteine protease, and NucB (biomembrane-degrading endonuclease), and the concentration is 1-10 mg / ml; the oxidized hyaluronic acid (OHA) has a molecular weight of 20-300 kDa and a concentration of 5-18 wt%.
[0011] Further, the storage tank is wrapped with a heat preservation layer, which includes a heat conducting wire and a temperature measuring needle, for heating and measuring the temperature of the solution in the storage tank to a set temperature; The end of the storage tank is provided with a stepper motor assembly for pushing the solution in the storage tank into the material mixing channel; The set temperature is 30-39℃.
[0012] Further, the material mixing channel is a "Y"-shaped conduit provided with a double-port end and a single-port end, the double-port end is connected to two storage tanks respectively, and the single-port end is connected to the injection hole.
[0013] Further, the outer wall of the catheter tube, the inner wall of the liquid reservoir and the inner wall of the material mixing channel are all provided with a super-hydrophilic coating; the super-hydrophilic coating is one or more of zwitterionic coating, acrylate coating and polyamine coating, preferably zwitterionic coating, and more preferably sulfobetaine-based zwitterionic polymer coating.
[0014] Further, the field of view acquisition module comprises a probe, a light source and an optical assembly; the probe is arranged at the front end; the light source is arranged on the probe, and the optical assembly is arranged on the probe and used for collecting image information and transmitting the image information to a display device.
[0015] A dual-phase in-situ injection-mixing type hydrogel adhesive coating material with biofilm breaking and killing functions is obtained by any of the preparation methods.
[0016] Compared with the prior art, the application has the following advantages: 1) The application uses dopamine hydrochloride, carboxymethyl chitosan, oxidized hyaluronic acid, antibiotics, EPS hydrolytic enzyme, etc. as raw materials, and combines chemical graft modification, blending, Schiff base reaction, etc. to obtain a dual-phase in-situ injection-mixing type hydrogel adhesive coating material with biofilm breaking and killing functions; and further, a new endoscopic active material delivery catheter is designed inspired by endoscopy technology, and a minimally invasive surgery technology is combined to form an application system matched with the adhesive coating material, and the above-mentioned raw material selection, process combination and system design are original.
[0017] 2) The application innovatively introduces a biofilm breaking and bacteria killing (referred to as breaking and killing) composite antibacterial strategy. For the clinical scene where bone infection has occurred, relevant reports show that the resistance of biofilm to antibiotics is more than 1000 times that of free bacteria, therefore, the application introduces EPS hydrolytic enzyme and antibiotics for use in combination, the physical structure of the formed biofilm is disintegrated by the EPS hydrolytic enzyme, the barrier protection effect of EPS in the biofilm is destroyed, and the bacteria inside the biofilm become free again; after the bacteria are exposed again, the antibiotics added in the adhesive coating can have a high bactericidal effect. The above-mentioned dual bactericidal strategy can solve the huge clinical problem that bone infection is difficult to cure after the formation of biofilm, and has great clinical significance and innovation.
[0018] 3) This invention innovatively introduces a two-component adhesive pre-solution and a "Y"-shaped material channel conduit. The two-component adhesive pre-solution consists of an oxidized hyaluronic acid solution carrying EPS hydrolase and a DA-CCs solution loaded with antibiotics. In use, the two solutions enter the endoscopic active material delivery conduit with the "Y"-shaped material mixing channel from two separate reservoirs. This allows the two-component adhesive pre-solution to mix at the intersection of the "Y"-shaped conduit and further mix completely during the subsequent single-channel delivery process, thereby achieving optimal gelation upon reaching the target location and ensuring uniform drug dispersion. The aforementioned two-component adhesive pre-solution is more stable and easier to store. It can be used after being mixed in the "Y"-shaped material channel. Compared with solutions of photocuring and oxidative cross-linking, it is more stable and does not require on-site preparation. At the same time, the two ends of the "Y"-shaped material channel are connected to two liquid reservoirs respectively, and the single end is connected to the conduit head. The two adhesive pre-solutions are stored in two liquid reservoirs respectively. The outside of the liquid reservoir is an insulation layer, and the rear end is a stepper motor assembly. The liquid reservoir has heating and insulation functions to maintain the internal solution temperature within the range of 30-39℃. In use, only a small incision is needed during minimally invasive surgery. The catheter is inserted into the incision, and its directional movement is controlled to reach the target area. Then, a stepper motor is controlled to advance the liquid front in the reservoir. The solution will automatically enter the "Y"-shaped material channel, mix, and be injected into the target location. It will then automatically solidify through a Schiff base reaction. Furthermore, the catechol groups on the DA-CCs molecules can achieve efficient adhesion to biological tissues and instruments, thus allowing the adhesive material to be fixed in the target area and continuously release the drug to exert its effect. Moreover, the polymers of the above two-component solution are oxidized hyaluronic acid and DA-CCs, which are both biodegradable macromolecules in the body. They will automatically degrade in the body after a certain period of time, eliminating the need for a second surgery to remove them and avoiding secondary harm and psychological burden on the patient.
[0019] 4) The endoscopic active material delivery catheter structure of this invention is designed based on the properties of the biphasic in-situ injection-mixing hydrogel adhesive coating material and the minimally invasive surgical scenario after biofilm formation. The endoscopic active material delivery catheter contains components such as a probe, light source, optical components, a reservoir, and a material mixing channel. One end of the catheter has a flexible, elastic section, and the outer side of the catheter, the reservoir, and the inner side of the material mixing channel are coated with a superhydrophilic coating. The probe, light source, and optical components together form a field-of-view acquisition module, which transmits the field of view after the catheter enters the organism. Furthermore, the flexible, elastic section ensures that the probe can rotate 360° omnidirectionally, making it flexible and convenient, and more conducive to the probe efficiently reaching the target position and acquiring the required field of view. Simultaneously, a superhydrophilic coating is provided on the outer side of the endoscopic active material delivery catheter, the reservoir, and the inner side of the material mixing channel. The superhydrophilic coating on the outer side of the catheter reduces friction between the catheter and tissue, thereby minimizing damage to biological tissues and allowing for smoother catheter movement within the tissue, improving surgical efficiency. Simultaneously, the hydrophilic coating reduces bacterial adhesion to the instrument upon reaching the infection site, preventing infection transfer and aggravation. The superhydrophilic coating on the inner side of the reservoir and material mixing channel prevents the adhesion and residue of the adhesive coating pre-solution on these areas, achieving a water contact angle of less than 10°, maintaining internal cleanliness, and facilitating cleaning and reuse of the instrument after use. These multiple superhydrophilic coatings on the instrument are designed based on specific application scenarios, demonstrating significant practicality and innovation.
[0020] 5) The biphasic bone repair adhesive coating material of this invention is easy to prepare. The mixing process can be achieved simply and efficiently by utilizing the principle of microfluidic mixing. The final curing process is also automatically completed in 1-3 minutes by Schiff base reaction (the gelation time can be controlled by adjusting the concentration of the two polymers and the ratio of carboxyl and amino groups). It is suitable for the efficient treatment of postoperative infection of bone implant devices in most parts of the body and has obvious convenience, practicality and universality. Attached Figure Description
[0021] Figure 1 This is a schematic diagram illustrating the preparation process of a biphase in-situ injection-mixed hydrogel adhesive coating material with biofilm-breaking function according to an embodiment of the present invention.
[0022] Figure 2 This is a schematic diagram of an endoscopic active material delivery conduit for a biphase in-situ injection-mixing hydrogel adhesive coating material with biofilm-breaking function according to an embodiment of the present invention. Figure 3 The results of bacterial coating of surrounding tissue fluid after using a biphasic in-situ injection-mixed hydrogel adhesive coating material with biofilm-breaking function according to an embodiment of the present invention are shown in Figure 1 (A is Comparative Example 1, B is Example 1). Detailed Implementation
[0023] The invention will be further illustrated below with specific examples.
[0024] Comparative Example 1: 1) Dissolve 10 wt% carboxymethyl chitosan (molecular weight 50,000, degree of carboxylation 80%) and 0.6 wt% dopamine hydrochloride in a mixed solvent of 20 wt% DMSO and 80 wt% deionized water. Under nitrogen protection, add 0.1 wt% EDC and stir for 30 min to activate. Then add 0.1 wt% NHS to carry out the coupling reaction for 24 hours. The product obtained by magnetic stirring at 400 rpm was dialyzed for 7 days with the solution changed 3 times a day. After lyophilization, the desired DA-CCs were obtained. 2) Prepare a DA-CCs solution loaded with 0.5wt% vancomycin (concentration of 15wt%) and an oxidized hyaluronic acid solution (molecular weight of 200kDa, concentration of 10wt%). 3) An endoscopic active material delivery conduit is designed for transporting adhesive coatings. The conduit contains a probe, light source, optical components, a liquid reservoir, and a material mixing channel. The front end of the conduit has a flexible section. The outer side of the conduit, the liquid reservoir, and the inner side of the material mixing channel are coated with a superhydrophilic coating of sulfobetaine (SBMA)-based zwitterionic polymer. The material mixing channel is a Y-shaped conduit with two ports connected to two liquid reservoirs and a single port connected to the head of the conduit. The two adhesive pre-solutions are stored in two liquid reservoirs. The outer side of the liquid reservoir is an insulation layer, and the rear end is a stepper motor assembly. The liquid reservoir has heating and insulation functions to maintain the internal solution temperature at 36-38℃. 4) Construct a rabbit fracture and infection model. The two solutions mentioned above are loaded into the two reservoirs of the catheter, respectively. The catheter is inserted into the infected site through minimally invasive surgery. The flexible tube segment at the front end of the catheter can ensure that the catheter probe can rotate 360°. The probe is rotated to obtain the field of view with the help of the light source and the data is transmitted to the display through the optical components. After the display shows that the probe has reached the target position, the stepper motor is controlled by the switch to push the solution in the two reservoirs along the "Y" shaped catheter until it is mixed at the intersection of the "Y" shaped catheter and injected into the target position. After in-situ gelation through Schiff base reaction (the solution gelation time is controlled to be 3 minutes), a hydrogel adhesive coating is obtained to achieve wound closure.
[0025] 5) The gel bonding strength was tested using a universal testing machine, and the bonding strength with titanium alloy (TC4) was approximately 23.6 kPa. The extract of the above composite hydrogel material was co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 7 days, and the cell viability was approximately 89.2%. Gel discs with a diameter of 1 cm were prepared for an inhibition zone experiment, and the inhibition zone area was approximately 3.56 cm². 2Two weeks after the sample was injected into the rabbit fracture and infection model, redness and swelling persisted around the surgical site. Upon opening, the internal tissue showed obvious inflammatory tissue and foreign secretions. Bacterial culture of the secretions revealed a large number of bacteria. Figure 3 A in the middle indicates that the biofilm may not have been destroyed and the infection has not been cured; Micro-CT shows poor fracture healing.
[0026] Example 1: 1) Dissolve 10 wt% carboxymethyl chitosan (molecular weight 50,000, degree of carboxylation 80%) and 0.6 wt% dopamine hydrochloride in a mixed solvent of 20 wt% DMSO and 80 wt% deionized water. Under nitrogen protection, add 0.1 wt% EDC and stir for 30 min to activate. Then add 0.1 wt% NHS to carry out the coupling reaction for 24 hours. The product obtained by magnetic stirring at 400 rpm was dialyzed for 7 days with the solution changed 3 times a day. After lyophilization, the desired DA-CCs were obtained. 2) Prepare a DA-CCs solution loaded with 0.5wt% vancomycin (concentration 15wt%) and an oxidized hyaluronic acid solution loaded with 8mg / ml EPS hydrolase dispersin B (molecular weight 200kDa, concentration 10wt%). 3) An endoscopic active material delivery conduit is designed for transporting adhesive coatings. The conduit contains a probe, light source, optical components, a liquid reservoir, and a material mixing channel. The front end of the conduit has a flexible section. The outer side of the conduit, the liquid reservoir, and the inner side of the material mixing channel are coated with a superhydrophilic coating of sulfobetaine (SBMA)-based zwitterionic polymer. The material mixing channel is a Y-shaped conduit with two ports connected to two liquid reservoirs and a single port connected to the head of the conduit. The two adhesive pre-solutions are stored in two liquid reservoirs. The outer side of the liquid reservoir is an insulation layer, and the rear end is a stepper motor assembly. The liquid reservoir has heating and insulation functions to maintain the internal solution temperature at 36-38℃. 4) Construct a rabbit fracture and infection model. The two solutions mentioned above are loaded into the two reservoirs of the catheter, respectively. The catheter is inserted into the infection site through minimally invasive surgery. The flexible tube segment at the front end of the catheter can ensure that the probe at the front end of the catheter can rotate 360°. The probe is rotated to obtain the field of view with the help of the light source and the data is transmitted to the display through the optical components. After the display shows that the probe has reached the target position, the stepper motor is controlled by the switch to push the solution in the two reservoirs along the "Y" shaped catheter until it is mixed at the intersection of the "Y" shaped catheter and injected into the target position. After in-situ gelation through Schiff base reaction (the solution gelation time is controlled to be 3 minutes), a biphasic in-situ injection-mixed hydrogel adhesive coating with biofilm destruction function is obtained to achieve wound closure.
[0027] 5) Compared to Comparative Example 1, this embodiment added EPS hydrolase to the hydrogel adhesive material. The gel bonding strength was tested using a universal testing machine, and the bonding strength with titanium alloy (TC4) was approximately 21.8 kPa. After co-culturing the extract of the above composite hydrogel material with bone marrow mesenchymal stem cells (BMSCs) for 7 days, the cell viability was approximately 87.1%. An inhibition zone experiment was conducted on gel discs with a diameter of 1 cm, and the inhibition zone area was approximately 3.37 cm². 2 Two weeks after the sample was injected into the rabbit fracture and infection model, the redness and swelling at the surgical site had largely subsided. Upon opening the wound, there was virtually no inflammatory tissue inside. Bacterial smear culture of the surrounding tissue fluid was performed. Figure 3 In the B sample, the number of bacteria was far less than in the control sample 1, indicating that the infection was significantly suppressed; Micro-CT showed that the fracture was beginning to show a healing trend.
[0028] Example 2: 1) Dissolve 10 wt% carboxymethyl chitosan (molecular weight 50,000, degree of carboxylation 80%) and 0.6 wt% dopamine hydrochloride in a mixed solvent of 20 wt% DMSO and 80 wt% deionized water. Under nitrogen protection, add 0.1 wt% EDC and stir for 30 min to activate. Then add 0.1 wt% NHS to carry out the coupling reaction for 24 hours. The product obtained by magnetic stirring at 400 rpm was dialyzed for 7 days with the solution changed 3 times a day. After lyophilization, the desired DA-CCs were obtained. 2) Prepare a DA-CCs solution loaded with 0.5wt% vancomycin (concentration 15wt%) and an oxidized hyaluronic acid solution loaded with 8mg / ml EPS hydrolase dispersin B (molecular weight 200kDa, concentration 10wt%). 3) Design an endoscopic active material delivery conduit for transporting adhesive coatings. The conduit is equipped with a probe, light source, optical components, liquid reservoir, material mixing channel, and other components. The front end of the conduit is equipped with a flexible tube section. The material mixing channel is a "Y" shaped conduit with two ends connected to two liquid reservoirs and a single end connected to the head of the conduit. The two adhesive pre-solutions are stored in the two liquid reservoirs respectively. The outside of the liquid reservoir is an insulation layer, and the rear end is a stepper motor assembly. The liquid reservoir has heating and insulation functions to maintain the internal solution temperature at 36-38℃. 4) Construct a rabbit fracture and infection model. The two solutions mentioned above are loaded into the two reservoirs of the catheter, respectively. The catheter is inserted into the infected site through minimally invasive surgery. The flexible tube segment at the front end of the catheter can ensure that the probe at the front end of the catheter can rotate 360°. The probe is rotated to obtain the field of view with the help of the light source and the data is transmitted to the display through the optical components. After the display shows that the probe has reached the target position, the stepper motor is controlled by the switch to push the solution in the two reservoirs along the "Y" shaped catheter until it is mixed at the intersection of the "Y" shaped catheter and injected into the target position. After in-situ gelation through Schiff base reaction (the solution gelation time is controlled to be 3 minutes), a biphasic in-situ injection-mixed hydrogel adhesive coating with biofilm destruction function is obtained to achieve wound closure.
[0029] 5) Compared to Example 1, this example reduces the design of superhydrophilic coatings on the outer side of the endoscopic active material delivery catheter, the reservoir, and the inner side of the material mixing channel. The gel bonding strength was tested using a universal testing machine; the bonding strength with titanium alloy (TC4) was approximately 22.3 kPa. After co-culturing the extract of the above composite hydrogel material with bone marrow mesenchymal stem cells (BMSCs) for 7 days, the cell viability was approximately 88.4%. An inhibition zone experiment was conducted on gel discs with a diameter of 1 cm; the inhibition zone area was approximately 3.44 cm². 2 When the sample was injected into the rabbit fracture and infection model, the smoothness of the operation decreased significantly, and sometimes blockage occurred. Two weeks after the operation, the redness and swelling at the surgical site had basically disappeared. After opening the wound, there was basically no inflammatory tissue inside. The bacterial smear culture of the surrounding tissue fluid showed that the number of bacteria was slightly higher than in Example 1, and the infection was significantly inhibited. Micro-CT showed that the fracture began to show a healing trend.
[0030] Example 3: 1) Dissolve 10 wt% carboxymethyl chitosan (molecular weight 50,000, degree of carboxylation 80%) and 0.6 wt% dopamine hydrochloride in a mixed solvent of 20 wt% DMSO and 80 wt% deionized water. Under nitrogen protection, add 0.1 wt% EDC and stir for 30 min to activate. Then add 0.1 wt% NHS to carry out the coupling reaction for 24 hours. The product obtained by magnetic stirring at 400 rpm was dialyzed for 7 days with the solution changed 3 times a day. After lyophilization, the desired DA-CCs were obtained. 2) Prepare a DA-CCs solution loaded with 0.5wt% vancomycin (concentration 15wt%) and an oxidized hyaluronic acid solution loaded with 8mg / ml EPS hydrolase dispersin B (molecular weight 200kDa, concentration 10wt%). 3) An endoscopic active material delivery conduit is designed for transporting adhesive coatings. The conduit is equipped with a probe, light source, optical components, and a liquid reservoir. The front end of the conduit is equipped with a flexible tube section. The outer side of the conduit and the inner side of the liquid reservoir are coated with a superhydrophilic coating of sulfobetaine (SBMA)-based zwitterionic polymer. The two adhesive pre-solutions are stored in two liquid reservoirs respectively. The outer side of the liquid reservoir is an insulation layer, and the rear end is a stepper motor assembly. The liquid reservoir has heating and insulation functions to maintain the internal solution temperature at 36-38℃. 4) Construct a rabbit fracture and infection model. The two solutions mentioned above are loaded into the two reservoirs of the catheter, respectively. The catheter is inserted into the infected site through minimally invasive surgery. The flexible tube segment at the front end of the catheter can ensure that the probe at the front end of the catheter can rotate 360°. The probe is rotated to obtain the field of view with the help of the light source and the data is transmitted to the display through the optical components. After the display shows that the probe has reached the target position, the stepper motor is controlled by the switch to push the solution in the two reservoirs forward along the straight catheter. After being injected into the target position, the solution is gelled in situ through Schiff base reaction (the gelation time of the solution is controlled to be 3 minutes) to obtain an adhesive coating and achieve wound closure.
[0031] 5) Compared to Example 1, this example eliminates the "Y"-shaped conduit design for the material mixing channel. The solution is injected through a straight conduit and mixed at the target location. The gel bonding strength was tested using a universal testing machine; the bonding strength with titanium alloy (TC4) was approximately 25.4 kPa. The extract of the above composite hydrogel material was co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 7 days, and the cell viability was approximately 90.0%. Gel discs with a diameter of 1 cm were prepared for an inhibition zone experiment; the inhibition zone area was approximately 3.58 cm². 2 When the sample was injected into the rabbit fracture and infection model, due to the lack of pre-mixing of the solution, the gelation at the surgical site was insufficient, causing the solution to flow into the surrounding tissue and fail to adhere well to the instrument surface. Two weeks after the operation, there was still obvious redness and swelling at the surgical site, and there was still inflammatory tissue inside after opening the wound. Bacterial smear culture of the surrounding tissue fluid showed a large number of bacteria, indicating that the infection was not cured. Micro-CT showed poor fracture healing.
Claims
1. A method for preparing a biphase in-situ injection-mixed hydrogel adhesive coating material with biofilm-breaking function, characterized in that, Includes the following steps: 1) Prepare a DA-CCs solution loaded with antibiotics and an oxidized hyaluronic acid solution loaded with EPS hydrolase. 2) The two solutions obtained in step 1) are mixed and injected into the surface of the instrument at the site of infection using an endoscopic active material delivery catheter. After in-situ gelation by Schiff base reaction, a hydrogel adhesive coating material is obtained. The endoscopic active material delivery conduit includes: a conduit body, a field of view acquisition module, a reservoir, a material mixing channel, an injection port, and a conduit controller assembly; One end of the catheter body is provided with an elastic tube section, which serves as the forward end; The field of view acquisition module is located at the end of the forward end and is used to acquire and transmit image information to the display device; Two reservoirs are installed in the tubing body to hold the DA-CCs solution loaded with antibiotics obtained in step 1) and the oxidized hyaluronic acid solution loaded with EPS hydrolase, respectively. The injection hole is located at the end of the forward end; The material mixing channel is disposed in the conduit body and is used to mix the solutions in the two reservoirs and output them from the injection port. The conduit controller assembly is used to achieve bending control of the elastic conduit segment.
2. The preparation method according to claim 1, characterized in that, In step 1), the preparation method of the DA-CCs is as follows: Dopamine hydrochloride was used to modify carboxymethyl chitosan with catechol to obtain DA-CCs. Specifically, carboxymethyl chitosan and dopamine hydrochloride were dissolved in a solvent, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide was added to the solvent under nitrogen protection and stirred for 30-60 min to activate it. Then, N-hydroxysuccinimide was added to carry out a coupling reaction. The product was dialyzed and lyophilized to obtain the DA-CCs.
3. The preparation method according to claim 2, characterized in that, The concentration of dopamine hydrochloride is 0.4-1.0 wt%, the molecular weight of carboxymethyl chitosan is 2000-50000, the degree of carboxylation is 60-90%, and the concentration is 5-20 wt%. The solvent is a mixture of DMSO and deionized water in a ratio of 20 wt% DMSO and 80 wt% deionized water. The concentration of 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 0.05-0.12 wt%, and the concentration of N-hydroxysuccinimide is 0.04-0.12 wt%. The coupling reaction time is 12-48 hours, and the magnetic stirring is performed at 200-400 rpm during the reaction. After the reaction, the product is dialyzed with ultrapure water for 3-7 days, with the solution changed 3-5 times a day.
4. The preparation method according to claim 1, characterized in that, In step 1), the concentration of DA-CCs is 5-22 wt%; the antibiotic is one or more of glycopeptides, carbapenems, and quinolones, and the amount added is 0.5-1 wt%.
5. The preparation method according to claim 1, characterized in that, In step 1), the EPS hydrolase is one or more of PgaB, alginate hydrolase, linear glycoside hydrolase, β-(1,3)glucan glycoside hydrolase, dispersin B, Proteinase K, Staphopain A, Staphopain B, Streptococcal cysteine protease, and NucB, with a concentration of 1-10 mg / ml; the molecular weight of oxidized hyaluronic acid is 20-300 kDa, and the concentration is 5-18 wt%.
6. The preparation method according to claim 1, characterized in that, The outside of the liquid reservoir is wrapped with a heat insulation layer, which includes a heat-conducting wire and a temperature measuring needle for heating and measuring the temperature of the solution inside the liquid reservoir to a set temperature. The end of the liquid reservoir is equipped with a stepper motor assembly for pushing the solution in the liquid reservoir into the material mixing channel; The set temperature is 30-39℃.
7. The preparation method according to claim 1, characterized in that, The material mixing channel is a "Y"-shaped conduit with a double-port end and a single-port end. The double-port end is connected to two liquid reservoirs respectively, and the single-port end is connected to the injection port.
8. The preparation method according to claim 1, characterized in that, The outer wall of the conduit, the inner wall of the reservoir, and the inner wall of the material mixing channel are all provided with a superhydrophilic coating; the superhydrophilic coating is one or more of zwitterionic coatings, acrylate coatings, and polyamine coatings.
9. The preparation method according to claim 1, characterized in that, The field of view acquisition module includes: a probe, a light source, and an optical component; the probe is disposed at the end of the forward-facing end; the light source is disposed on the probe, and the optical component is disposed on the probe, for acquiring image information and transmitting it to a display device.
10. A biphase in-situ injection-mixed hydrogel adhesive coating material with biofilm-breaking function, characterized in that, It is obtained by the preparation method described in any one of claims 1-9.
Citation Information
Patent Citations
Injectable hydrogel, preparation method and application thereof
CN111588916A
High-adhesion bi-component self-crosslinking digestive tract injury mucosa protection glue and application thereof
CN112494711A
In-situ injectable bone repair adhesive material with double-sequence osteogenesis promoting function as well as preparation method and application of in-situ injectable bone repair adhesive material
CN119386249A